Developing University Libraries by Using Internet of Things (IOT) Mechanism - Faris Sattar Hadi (Genius Journals, 2022)
All facets of our lives and activities have been significantly impacted by the introduction of clever new technology, smart mobile connections, and online services. The world around us is also greatly impacted by this development. In the modern world, libraries and library services are very influential. The current study's objective is to investigate how Internet of Things, a novel technology, is used in libraries and educational facilities. Librarians should be aware of the various features of IOT in libraries and services since new technologies have raised user expectations from library services. They should also receive training on user behavior and IOT security concerns in libraries. Through construction, collection management, training, data security, information literacy, and other factors, the IOT will continue to have an impact on libraries and the services they provide. This paper also aims to familiarize readers with emerging IOT technologies that libraries might employ to enhance user satisfaction and provide better services.
Keywords: University Library; Internet of Things; Information; Technologies